(3ELGRIs - (3YHO GdbGOQ Hf jMji GdHUjQ GdTGej GdHUQj GdfLOjs
(3ChdgG (B:s
(3GdMeO ddg GdgGOi HdWaI Edi GdQTGO , GdeJaVd Ydi YHGOg HLYd SdSdI GdESfGO HQhGjI GdKaGJ GdCLdI ehUhdg GdN s
(3BNQgG (B:s
(3bGd Pdc Haeg hQbe HCeQg GdTjN YHO GdbGOQ Hf jMji GdHUjQ GdTGei GdCUd hGdHUQi GdehdO hGdfLOi efTC Ke GdTGei QMdI hJMUjdG s
(3Edi JdejPg GdTjN Ndjd NWjH Hf eMeO Hf jSf GdSGeQi GdHZOGOi GdMfais
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B6 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs